Pure double-layer bubbles in quadratic F ( R ) gravity - Eiroa, Ernesto Fabian (2017)
We present a class of spherically symmetric spacetimes corresponding tobubbles separating two regions with constant values of the scalar curvature, orequivalently with two different cosmological constants, in quadratic F(R)theory. The bubbles are obtained by means of the junction formalism, and thematching hypersurface supports in general a thin shell and a gravitationaldouble layer. In particular, we find that pure double layers are possible forappropriate values of the parameters of the model whenever the quadraticcoefficient is negative. This is the first example of a pure double layer in agravitational theory.